2013
DOI: 10.1093/hmg/ddt460
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the repeat expansion size in C9orf72 in amyotrophic lateral sclerosis and frontotemporal dementia

Abstract: Hexanucleotide repeat expansions within the C9orf72 gene are the most important genetic cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). The difficulty of developing a precise method to determine the expansion size has hampered the study of possible correlations between the hexanucleotide repeat number and clinical phenotype. Here we characterize, through a new non-radioactive Southern blot protocol, the expansion size range in a series of 38 ALS and 22 FTD heterozygous carriers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
88
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(95 citation statements)
references
References 18 publications
4
88
1
2
Order By: Relevance
“…Of note, unequivocal evidence indicates that repeat expansion in the atypical range might be genetically unstable and expand upon subsequent generations [35,68,71]; therefore, it may be considered analogous to Fragile X, i.e., a "pre-mutation" [35]. In our study, methylation of the 5′ portion of the C9orf72 repeat expansion was identified in the 2 positive cases with large repeat expansions, and found to be absent in the single case within the atypical range (80-100 repeats) expansion and in the A limitation of this study is the lack of clinical information precluding phenotype-genotype correlation of our C9orf72 repeat expansion positive and intermediate cases, and confirmation that our cases truly represented HD phenocopies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, unequivocal evidence indicates that repeat expansion in the atypical range might be genetically unstable and expand upon subsequent generations [35,68,71]; therefore, it may be considered analogous to Fragile X, i.e., a "pre-mutation" [35]. In our study, methylation of the 5′ portion of the C9orf72 repeat expansion was identified in the 2 positive cases with large repeat expansions, and found to be absent in the single case within the atypical range (80-100 repeats) expansion and in the A limitation of this study is the lack of clinical information precluding phenotype-genotype correlation of our C9orf72 repeat expansion positive and intermediate cases, and confirmation that our cases truly represented HD phenocopies.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to HD, for which the clinical significance of repeat size ranges is well characterized, the cutoff for pathogenic C9orf72 repeat expansion is currently undefined. Although repeat expansions in the range of hundreds to thousands are typically considered pathogenic [1,[68][69][70], the lower threshold that defines a pathologic repeat size is not established [1,27,35,37,69,71]. The reportable range of this assay was based on initial studies [2,3], and alleles were considered as follows: normal range (< 20 repeats), intermediate range (20- Any homozygous samples and intermediate cases by the genotyping PCR assay are routinely evaluated with a follow-up Southern blot to exclude the possibility of an expanded allele that was not detected by the PCR assay, as currently recommended [72].…”
Section: C9orf72mentioning
confidence: 99%
“…It has been suggested that in individual patients carrying the C9orf72 HRE, cells from different tissues or different regions of the brain exhibit varying lengths of repeats. [48][49][50] Irrespective of the neuronal or glial origins of these brain cells, the repeat instability could arise during somatic cell division, post-mitotic stages, or both, as seen in other repeat expansion diseases.…”
Section: C9orf72 Repeat Expansion Diseasesmentioning
confidence: 99%
“…For example, does the number of repeats affect age at onset or disease severity (as in HD)? This has been difficult to assess due to technical limitations in the resolution power of southern blotting, though refined techniques now make determination of expansion length more accurate [6,10,62], but still no associations with age at onset or disease severity have been detected [17,62]. However, such observations are confounded by regional mosaicism, with reports that longer repeat lengths in cerebellum are associated with a longer, not shorter, duration (see Cooper-Knock).…”
mentioning
confidence: 99%
“…Secondly, given that there appears to be no consistent (group) differences in repeat length between ALS and FTLD cases [17,62] What do we know regarding how possession of the expansion might cause disease? We know that C9ORF72 is variably transcribed with at least three major transcripts being formed (see Stepto), and while there is evidence for loss of transcription with haploinsufficiency [7,16], it is notable that rare cases of homozygosity for expansion in C9ORF72 do not display a more aggressive clinical phenotype, and appear not to accrue greater pathology [20].…”
mentioning
confidence: 99%